Genome wide identification of lncRNAs and circRNAs having regulatory role in fruit shelf life in health crop cucumber (Cucumis sativus L.) - Dey, Shyam S.; Sharma, Parva Kumar; Munshi, A. D.; Jaiswal, Sarika; Behera, T. K.; Kumari, Khushboo; G., Boopalakrishnan; Iquebal, Mir Asif; Bhattacharya, R. C.; Rai, Anil; Kumar, Dinesh (Frontiers in Plant Science, 2022)
Cucumber is an extremely perishable vegetable and under room condition, fruits become unfit for consumption 2-3 days after harvesting. One natural variant, DC-48 with extended shelf-life was identified, fruits of which can be stored up to 10-15 days under room temperature. The genes involved for this economically important trait are regulated by non-coding RNAs. The study aims to identify the long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) by taking two contrasting genotypes, DC-48 and DC-83 at two different fruit developmental stages. The upper epidermis of the fruits was collected at 5 days and 10 days after pollination (DAP) for high throughput RNA sequencing. The differential expression analysis was performed to identify differentially expressed (DE) lncRNAs and circRNAs along with the network analysis of lncRNA, miRNA, circRNA and mRNA interactions. A total of 97 DElncRNAs were identified where 18 were common under both the developmental stages (8 down regulated and 10 upregulated). Based on the back-spliced reads, 238 circRNAs were found to be distributed uniformly throughout the cucumber genomes with highest numbers (71) in chromosome 4. Majority of the circRNAs (49%) were exonic in origin followed by inter-genic (47%) and intronic (4%) origin. The genes related to fruit firmness, namely, polygalacturonase, expansin, pectate lyase and xyloglucan glycosyltransferase were present in the target sites and co-localised networks indicating the role of the lncRNA and circRNAs in their regulation. Genes related to fruit ripening, namely, Trehalose-6-phosphate synthase, Squamosa promoter binding protein, WRKY domain transcription factors, MADS box proteins, Abscisic stress ripening inhibitors and different classes of heat shock proteins (HSPs) were also found to be regulated by the identified lncRNA and circRNAs. Besides, ethylene biosynthesis and chlorophyll metabolisms were also found to be regulated by DElncRNAs and circRNAs. A total of 17 transcripts were also successfully validated through RT PCR data. These results would help the breeders to identify the complex molecular network and regulatory role of the lncRNAs and circRNAs in determining the shelf-life in cucumber.